Assessing psychological and supportive care needs in glioma patients – feasibility study on the use of the Supportive Care Needs Survey Short Form (SCNS‐SF34‐G) and the Supportive Care Needs Survey Screening Tool (SCNS‐ST9) in clinical practice. (24th October 2016) - Renovanz, M.; Hickmann, A.‐K.; Coburger, J.; Kohlmann, K.; Janko, M.; Reuter, A.‐K.; Keric, N.; Nadji‐Ohl, M.; König, J.; Singer, S.; Giese, A.; Hechtner, M.
Abstract : Neuro‐oncological patients experience high symptom and psychosocial burden. The aim was to test feasibility and practicability of the Supportive Care Needs Survey Short Form (SCNS‐SF34‐G) and the SCNS‐Screening Tool (SCNS‐ST9) to assess supportive care needs of neuro‐oncological patients in clinical routine. A total of 173 patients, most with a primary diagnosis of high‐grade glioma (81%), were assessed first using SCNS‐SF34‐G in comparison to two well‐established patient‐reported outcome measures, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQC30 + QLQ‐BN20) and Distress Thermometer (DT). In a follow‐up assessment, SCNS‐ST9 was used in a subgroup ( n = 90). Questionnaires were completed either with personal guidance offered (group A) or by patients alone (group B). Feasibility was compared between instruments and groups for possible associations with patient and treatment‐related factors. Missing values occurred in similar frequencies in all instruments. Errors in completion occurred in SCNS‐SF34‐G in 20% and in SCNS‐ST9 in 16%; difficulties in completion were observed more often in SCNS‐SF34‐G and SCNS‐ST9 (39%) compared to DT and EORTC (13%, p < .001). Distress was found to be associated with difficulties in completion of SCNS (OR 1.4, [95% CI 1.1–1.9], p = .013). SCNS‐SF34 and SCNS‐ST9 are suitable tools for glioma patients as long as personal guidance is offered.